The case for biotechnology in Africa´s agriculture - Alhassan, Walter S. (Technical Centre for Agricultural and Rural Cooperation, 2003)
The challenge: Food production and poverty reduction remain the primary goals of efforts to advance socio-economic development in Africa and the well-being of its people. The scope for increasing food production through area expansion, the use of agro-chemicals and irrigation is limited. Intensification of production holds the key for Africa's future. The challenge is to develop technologies for intensifying agriculture for resource-poor farmers that use minimal external inputs in environments that are already bedevilled by so many biotic and abiotic stresses. Modern biotechnology has been identified as the most potent technology for rescuing Africa from the effects of food shortages, just as the 'green revolution' did for the countries of Southeast Asia in the 1970s.